The task of inventing Chile - Laborde, Miguel (Base Diseño e Innovación, 2019)
In times when an international and cosmopolitan culture dominates the setting, in the context of a xenophobic and racist nationalism, national identities run the risk of becoming ethnic fashions, barely useful for tourism marketing. Heritage is put on trial and its role of disguising history is no longer accepted.